Health‐related Quality of Life in Patients with Metastatic Spinal Cord Compression - Morgen, Søren S (Orthop Surg, 2016)
OBJECTIVE: Improvements in cancer treatment have resulted in an increased number of patients with metastatic spinal cord compression (MSCC). Because patients with MSCC often have a limited expected survival time, maintenance of a high functional level and quality of life are important. However, there is limited information about health‐related quality of life (HRQoL) in patients with MSCC. The aim of this study was to examine the feasibility of routine assessment of HRQoL based on the Euroqol‐5 dimensions (EQ‐5D) questionnaire in a cohort of patients consecutively admitted for evaluation of acute symptoms of MSCC. METHODS: From 1 January to 31 December 2011, 544 patients diagnosed with acute symptoms of MSCC were consecutively enrolled in a cohort study. All patients were evaluated through a centralized referral system at one treatment facility. Data were prospectively registered, the variables age, sex, primary oncologic diagnosis, Tokuhashi Revised score, EQ‐5D score and treatment modality being recorded on admission. The study patients were treated conservatively with radiotherapy alone or with surgery and subsequent radiotherapy. The EQ‐5D questionnaire was administered on admission (baseline) and 6, 12, 26 and 52 weeks after admission. Response rates, completion rates and HRQoL scores were analyzed by relevant subgroups. Response rates were based on all questionnaires returned regardless of whether or not they had been completed, whereas completion rates were based on fully completed questionnaires (i.e., containing responses to all five questions. RESULTS: The mean age was 65 years (range, 20–95 years); 57% of the patients were men. The overall response rate to the Euroqol‐5 dimensions (EQ‐5D) questionnaires was 84% and the overall completion rate 72%. At baseline, mean EQ‐5D scores were significantly lower for patients treated with surgery and subsequent radiotherapy 0.28 (95% CI, 0.19–0.36) than for those treated with radiotherapy alone 0.42 (95% CI, 0.38–0.46). At the one‐year follow‐up, the mean EQ‐5D scores had improved to 0.71 (95% CI, 0.64–0.77) for patients treated with surgery and subsequent radiotherapy and 0.63 (95% CI, 0.56–0.70) for patients treated with radiotherapy alone. CONCLUSIONS: Measurement of HRQoL in patients consecutively admitted for evaluation of acute symptoms of MSCC is feasible and detects significant changes over time between treatment modalities and different strata of expected survival.